Ecotourism Potentials, Challenges and Prospects of Maze National Park, South West Ethiopia (Global Journal of Management and Business Research, 2017)
The study was carried out in Maze National Park in the South West Ethiopia to identify the opportunities challenges and prospects for sustainable ecotourism in the Park The study employed survey design using exploratory indepth interview focus group discussion and participant s observation Data was collected from primary and secondary sources Interviews indicated wildlife savanna plains landscape bilbo hot spring wonja stone cave religious trees and rivers were the major ecotourism potentials of the park Focus group discussions revealed population pressure wildlife death and migration conflict of interest poor political commitment and climate change as major challenges for ecotourism in Maze National Park Among others organizing staff profile community participation and benefit sharing adequate budget allocation improved livestock production building water points harvesting timber and non-timber products and infrastructure development were identified to be the main prospects of the park Therefore the results of the present study underpins that sustainable ecotourism in Maze National Park will be realized if the immense potentials of the park are well-managed its challenges are well-addressed and its prospects are well-embraced and multilateral action plans for ecotourism development become a guiding principle among all stakeholders
Keywords: Community-based ecotourism; Ecotourism; Male; Maze National Park; Sustainable ecotourism; Tourism